Community-Based Ecotourism In Indonesia: A Case Study In Nglanggeran Tourism Village - Muhammad Iqbal; Yunita Elianda; Nurhadiyanti Nurhadiyanti; Ali Akbar (Lembaga Administrasi Negara, 2021)
Nglanggeran Tourism Village has now successfully developed a tourism village with the concept of ecotourism. The purpose of this study is to analyze the involvement of the community in encouraging the strengthening of ecotourism in Nglanggeran village. The research method approach was carried out qualitative by using NVivio 12 Plus data analysis. The findings in this research are Youth Organizations, Tourism Management, Small Business Actors, Native, and Pokdarwis (Tourism Awareness Group) have a vital role in tourism development in Nglanggran Village.Keywords: Community-Based Tourism; Ecotourism; Nglanggeran Tourism Village; Yogyakarta